P163 Staff experience of routine breathlessness assessment on a virtual covid ward. (11th November 2022) - Rhatigan, K; Koulopoulou, M; Fenton, J; Ramos-Smyth, S; Ford-Adams, M; Patel, A; Cho, PSP; Patel, I; Birring, SS; Jolley, CJ
Abstract : Introduction: Our hospital redeployed healthcare professionals to implement a telephone-based Virtual Covid Ward (VCW) during the COVID-19 pandemic. Standardised clinical assessment included numeric (0 – 10) rating scales (NRS) for breathlessness and cough, and pulse oximetry. Aims and objectives: To assess staff experience of routine breathlessness documentation by surveying feedback on the clinical effectiveness of assessment tools used in the VCW. Methods: Data were obtained from an anonymous online survey distributed to VCW staff, summarised in themes and analysed with descriptive statistics. Results: 9/19 VCW staff completed the survey; 9 female; 5 nurses, 3 physiotherapists, 1 Operating Department Practitioner; 8 were senior, 1 junior. 100% had acute or respiratory medicine experience, 66% had experience in remote assessments. 100% reported absence of breathlessness at rest the most reassuring sign when discharging patients. 100% confidence when assessing breathlessness over the phone. 100% felt breathlessness was a 'red flag'. 66% found the breathlessness NRS useful and 67% found the cough NRS useful. 89% believed patients' responses were meaningful at least half the time. 78% believed patients overestimated the breathlessness score at least half of the time and 55% believed patients underestimated respiratory distress. Conclusion: VCW staff were confident in assessing patients remotely and using the NRS. Staff found assessment of breathlessness useful in predicting adverse patient outcomes, but were less confident using the NRS (0–10) rating scale to quantify breathlessness was clinically valuable.